Different Trials in Mechanical Thrombectomy for Acute Ischemic Stroke - Gurung, Pritam; Shrestha, Bishal; Neupane, Anish; Rajbhandhari, Pravesh (Annapurna Journal of Health Sciences, 2023)
Acute Ischemic Stroke (AIS) is a leading cause of death and disability. It can be treated early with a favorable prognosis if intravenous recombinant tissue plasminogen activator (IV rt-PA) is given to eligible patients within 4.5 hours of its onset. For those patients who do not meet the criteria to undergo intravenous fibrinolysis, mechanical thrombectomy has been shown to be an effective alternative in patients presenting with occlusion of first segment of middle Cerebral artery (MCA) or of internal carotid artery (ICA), provided the intervention is performed within 24 hour according to previous trial. We herein review different randomized controlled trials on AIS undergoing mechanical thrombectomy.